Peran Kepala Sekolah Dalam Meningkatkan Prestasi Siswa Di SMA Negeri Keberbakatan Olahraga Provinsi Bengkulu - IS, Tuti Handayani; Lorita, Evi; Sariningsih, Marida; Ayu, Puja Putri (Professional: Jurnal Komunikasi dan Administrasi Publik, 2023)
This study aims to examine the influence of school principal leadership on the athletic achievements of students at the State High School for Sports Talents (SMAN Keberbakatan Olahraga) in Bengkulu Province. The research is grounded in the premise that school principals play a pivotal role as change agents in shaping an educational environment that promotes non-academic achievement, particularly in sports-oriented schools. A quantitative approach was used, employing a survey method with a sample of 76 students selected from a total population of 138. The primary instrument was a Likert-scale questionnaire measuring students' perceptions of leadership and their sports performance. The results reveal that the principal's leadership positively impacts student motivation, self-confidence, and athletic performance. Key leadership dimensions such as idealized influence, individualized consideration, inspirational motivation, and intellectual stimulation significantly contribute to student achievements in various sports disciplines such as futsal, taekwondo, and pencak silat. Statistical analysis using simple linear regression confirmed a significant relationship between principal leadership and student performance. This study recommends strengthening school principals' leadership capacity through managerial training and soft skills development in the context of sports education. Additionally, stronger synergy among school principals, coaches, and external stakeholders is essential to fully optimize student potential and elevate them to national and international sporting success.